The Influence of the Severity of Obstructive Sleep Apnea on the Incidence of Hypertension - Tjandra, Marchella; Moningkey , Shirley Ivonne; Lim , Hendyono (Medicinus, 2025)
Background : Hypertension is a condition where systolic blood pressure reaches 140 mmHg, and diastolic blood pressure reaches 90 mmHg. According to the Ministry of Health of Republic Indonesia, hypertension ranks third as a cause of death in Indonesia. Secondary hypertension arises from identifiable causes such as obstructive sleep apnea, renal vascular disease, hormonal contraceptives, endocrine disorders, stress-induced hypertension, pregnancy, burns, renal parenchymal disease, polycystic ovarian syndrome, preeclampsia, and specific medications like NSAIDs and antidepressants. Previous studies have recorded 83% Hypertension patients had OSA. Despite these findings, there are still contradictions in the literature (7), indicating the need for further research to explore the relationship between OSA and hypertension, as well as the impact of different types of OSA on hypertension. Methods : This research is an observational analytic study using a cross-sectional method. Medical status data and polysomnography results were collected from February to April 2024 at Siloam Hospitals Lippo Village. Data were processed using SPSS 23.0 and analyzed using the chi-square method. Significant variables will be further analyzed using logistic multivariate analysis. Result : There was an influence of the severity of Obstructive Sleep Apnea on the incidence of hypertension at Siloam Hospitals Lippo Village (OR=15.4, 95%CI 3.477 – 68.216; p-value=0.001). Besides the influence of the severity of Obstructive Sleep Apnea, other variables such as gender, BMI ≥ 23 kg/m², and a history of diabetes mellitus also affected the incidence of hypertension. Conclusion : The influence of the severity of Obstructive Sleep Apnea on the incidence of hypertension found in Siloam Hospitals Lippo Village.